Precipitation priority in 5083 Al-alloys containing small amounts of Cu or Zn. Issue 18 (12th December 2017) - Chen, Wei; Luo, Binghui; Gao, Yang; Bai, Zhenhai; Jing, Huibo; Zhao, Jingwei
ABSTRACT: This study investigated the precipitation priority in Al–Mg alloys modified by the addition of 0.8 wt-% Cu or Zn, revealing that both these alloys exhibit increased hardness and decreased corrosion resistance. Scanning electron microscopy, transmission electron microscopy, and high-angle annular dark field imaging show that the precipitation priority changed the main second-phase particles of Cu- and Zn-containing alloys. Additionally, thermodynamic data of these phases were calculated using a semi-empirical model, showing good agreement with the experimental results. This paper is part of a thematic issue on Light Alloys.